Cerium dioxide doped nickel phosphide cobalt loaded titanium carbide Mxene composite electrocatalytic material and preparation method thereof

By preparing ceria-doped nickel-cobalt phosphide-supported titanium carbide Mxene composites, the problems of limited resources and high cost of precious metal catalysts are solved, and the catalytic performance of cathodic hydrogen evolution and anode oxygen evolution reactions is achieved, and excellent catalytic activity and stability are demonstrated.

CN120536979APending Publication Date: 2025-08-26GANTRY LAB

Patent Information

Application Number
CN202511050527.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-29
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

In the prior art, the precious metal catalysts Pt/C and IrO2 show good catalytic performance in cathode hydrogen evolution reaction (HER) and anode oxygen evolution reaction (OER), but the resources are limited and costly, making it difficult to commercially apply. It is necessary to find efficient non-precious metal-based bifunctional catalysts.

Method used

The preparation method of ceria-doped nickel-cobalt phosphide loaded to titanium carbide Mxene composite was used to prepare single/small Ti3C2TxMXene by LiF+HCl etchant, and NiCoP nanoparticles were loaded on Ti3C2TxMXene by hydrothermal method and thermal phosphating process. CeO2NPs were attached to NiCoP and Ti3C2TxMXene to form CeO2-NiCoP/Ti3C2TxMXene composite material.

Benefits of technology

It has achieved excellent HER and OER catalytic activity and stability in alkaline media. CeO2-NiCoP/Ti3C2TxMXene composite material has low overpotential at 10 mA cm-2, has a small Tafel slope, a small charge transfer resistance, and a high retention rate of electrode activity within 25 h, demonstrating good catalyst stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120536979A_ABST
    Figure CN120536979A_ABST
Patent Text Reader

Abstract

The invention discloses a cerium dioxide doped nickel phosphide cobalt loaded titanium carbide Mxene composite electrocatalytic material and a preparation method thereof, and belongs to the technical field of electrocatalytic materials. According to the invention, single / few-layer Ti < 3 > C < 2 > T < x > MXene is successfully synthesized by adopting LiF + HCl as an etching agent through a simple in-situ generation method, and a terminal functional group on the surface of the Ti < 3 > C < 2 > T < x > MXene can attract metal active components; niCoP nano-particles are prepared through a hydrothermal method and a thermal phosphating process and are loaded on a few layers of Ti < 3 > C < 2 > T < x > M < Xene > material, CeO2 NPs are attached to NiCoP and Ti < 3 > C < 2 > T < x > M < Xene > sheet layers, and the difunctional CeO2-NiCoP / Ti < 3 > C < 2 > T < x > M < Xene > composite electro-catalytic material is obtained. The preparation method is simple and efficient; the prepared composite electro-catalytic material can show excellent HER and OER catalytic activity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalytic materials, and in particular relates to a cerium dioxide-doped nickel cobalt phosphide-loaded titanium carbide Mxene composite electrocatalytic material and a preparation method thereof. Background Art

[0002] In the context of a low-carbon or carbon-free economy, hydrogen energy is widely recognized as having the greatest potential for development. Due to its environmentally friendly combustion products and high energy density, it holds a crucial position in future energy development. Among the various methods for producing H2, water electrolysis using renewable energy to produce hydrogen (H2) and oxygen (O2) is a highly attractive carbon-free strategy. The combustion product of H2 is water, which allows for a cyclical cycle between the two, and meets economic and environmental requirements. However, catalysts must meet the requirements of both the cathode hydrogen evolution reaction (HER) and the anode oxygen evolution reaction (OER) to achieve good catalytic performance and stability. To date, Pt / C and IrO2 are considered the most effective HER and OER catalysts, but limited resources and high costs have prevented their commercial application. The key strategy is to identify efficient non-precious metal-based HER and OER catalysts, particularly bifunctional non-precious metal catalysts for overall water splitting. Summary of the Invention

[0003] The purpose of the present invention is to provide a cerium dioxide doped nickel cobalt phosphide loaded on titanium carbide Mxene composite electrocatalytic material and a preparation method thereof, the preparation method is simple and efficient; the prepared CeO2-NiCoP / Ti3C2T x MXene composite electrocatalytic materials can exhibit excellent catalytic activity and stability for HER and OER.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides a method for preparing a composite electrocatalytic material of cerium dioxide doped nickel cobalt phosphide loaded on titanium carbide Mxene, comprising the following steps: S1, using hydrochloric acid and lithium fluoride as etchants to etch in a polytetrafluoroethylene liner; S1-1. Dissolve lithium fluoride in an appropriate amount of hydrochloric acid solution and stir at 30-35°C for 10-15 minutes. Then add Ti3AlC2 MAX powder, raise the temperature to 35-40°C, and stir continuously at constant temperature for 36-48 hours to obtain a suspension. The entire reaction is carried out in a fume hood. S1-2, transferring the suspension obtained in step S1-1 to a centrifuge tube, and washing the suspension several times with deionized water through a centrifuge until the pH of the supernatant is 6.8-7, thereby obtaining precipitate I; S2. The precipitate I obtained in step S1 was dissolved in dimethyl sulfoxide, stirred at room temperature, and then the dimethyl sulfoxide was washed with deionized water to obtain precipitate II. The precipitate II was redispersed in deionized water and sonicated in the presence of argon to peel the multilayer material into a single layer or a few layers of MXene. The dark green upper suspension obtained by centrifugation was the single layer or few layers of Ti3C2T x MXene; S3, the Ti3C2T obtained in step S2 x The MXene suspension was diluted, and then nickel nitrate hexahydrate, cobalt nitrate hexahydrate, cerium nitrate hexahydrate, urea and NH4F were dissolved in an appropriate amount of diluted Ti3C2T x After magnetic stirring, the resulting mixture was transferred to an autoclave and kept at 110-130 °C for 10-14 h. It was then washed with deionized water and dried under vacuum. S4. The powder obtained in step S3 is placed in a tube furnace, Ar is introduced, and the mixture is reduced at 400-500°C for 1-3 hours, and then cooled to room temperature to obtain a precursor; a phosphating process is performed using sodium hypophosphite as a P source. The precursor and sodium hypophosphite are placed at both ends of a quartz tube, with the sodium hypophosphite at the upstream position. The mixture is heated to 300-400°C in a tube furnace under an Ar atmosphere, kept warm for 1-2 hours, and cooled to room temperature to obtain the target sample, which is named CeO2-NiCoP / Ti3C2T x MXene.

[0005] Preferably, in step S4, the mass ratio between the precursor and the sodium hypophosphite is 1:3; the heating rate in the tube furnace is set to 3°C min -1 .

[0006] Preferably, in step S4, the precursor is obtained by reducing the mixture at 450° C. for 2 h and then cooling the mixture to room temperature.

[0007] Preferably, in step S4, the quartz tube is heated to 350° C. in a tube furnace under an Ar atmosphere and kept at this temperature for 2 h.

[0008] Preferably, in step S3, the concentrations of nickel nitrate hexahydrate, cobalt nitrate hexahydrate, cerium nitrate hexahydrate, urea, and NH4F in the mixed solution are 0.014-0.017 mol / L, 0.028-0.034 mol / L, 0.002-0.0025 mol / L, 0.21-0.25 mol / L, and 0.1-0.125 mol / L, respectively; the mixture is kept at 120°C for 12 h, stirred for 30-35 min, and vacuum dried at 60°C.

[0009] Preferably, in step S2, the ultrasonication is performed in an ice bath throughout the entire process, with the ultrasonication temperature being lower than 20° C.; and the centrifugal speed is 8000-10000 r / min.

[0010] Preferably, in step S1-1, the molar ratio of Ti3AlC2MAX powder to lithium fluoride and hydrochloric acid is 1:15:47.

[0011] Preferably, in step S1-2, the centrifugal speed is 3000-12000 r / min, and the centrifugal time is 5-20 min.

[0012] In order to achieve the purpose of the invention, the present invention also provides a cerium dioxide-doped nickel cobalt phosphide loaded on titanium carbide Mxene composite electrocatalytic material prepared by the above preparation method.

[0013] The present invention successfully synthesized single / few layers of Ti3C2T by a simple in-situ generation method using LiF+HCl as an etchant. x MXene, to a certain extent, Ti3C2T x The end functional groups on the surface of MXene can attract metal active components. NiCoP nanoparticles were prepared by hydrothermal method and thermal phosphating process and loaded onto few-layer Ti3C2T x MXene materials, where CeO2 NPs are attached to NiCoP and Ti3C2T x On the MXene layer, a bifunctional CeO2-NiCoP / Ti3C2T x MXene composite electrocatalytic materials.

[0014] The present invention uses transition metals to replace the catalyst materials of precious metals to reduce the amount of precious metals used, and CeO2-NiCoP / Ti3C2T x MXene exhibits excellent bifunctional catalytic performance, that is, it exhibits good catalytic activity and stability for HER and OER. Characterization results show that the CeO2-NiCoP / Ti3C2T x HER performance of MXene composites in 1 M KOH solution at 10 mA cm -2 Under the condition of 147mV overpotential, the Tafel slope is 134mV dec. -1 , evaluated CeO2-NiCoP / Ti3C2T in alkaline medium x The HER stability of MXene was tested for 25 h, and the electrode activity was still maintained at 84.6%; the OER performance was 10 mA cm in 1 M KOH solution. -2 Under the condition of 100 nm, the overpotential is only 287 mV and the Tafel slope is 64 mV dec. -1, and also has a small charge transfer resistance (Rct), showing excellent hydrogen and oxygen evolution activity. CeO2-NiCoP / Ti3C2T was evaluated in alkaline medium. x The OER stability of MXene was tested for up to 25 hours, and the electrode activity was still maintained at 93.6%, indicating that the catalyst of the present invention has good stability, better retention of hydrogen and oxygen evolution performance, and long-term stability. This is due to the synergistic effect between the two metals, and the combination of oxides and bimetallic phosphides can obtain a composite material with excellent catalytic activity, conductivity and stability as well as the hydrophilicity of the oxide. x On the MXene matrix material, rare earth oxide CeO2 fully utilizes its advantages such as good stability, good hydrophilicity, strong oxygen storage capacity, reversible exchange of surface oxygen ions and good electronic / ionic conductivity. It can be used as a promoter to regulate the electrocatalytic properties of various transition metals and optimize the catalytic activity of phosphides (NiCoP). BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 CeO2-NiCoP / Ti3C2T prepared in Example 1 x XRD pattern of MXene; Figure 2 CeO2-NiCoP / Ti3C2T prepared in Example 1 x SEM images of MXene; (a) scale bar is 200 nm, (b) scale bar is 500 nm; Figure 3 CeO2-NiCoP / Ti3C2T prepared in Example 1 x HRTEM images of MXene; (a) scale is 5 nm, (b) scale is 10 nm; Figure 4 CeO2-NiCoP / Ti3C2T prepared in Example 1 x HAADF-STEM image and elemental mapping distribution of MXene; Figure 5 CeO2-NiCoP / Ti3C2T prepared in Example 1 x EDS images of MXene; Figure 6 CeO2-NiCoP / Ti3C2T prepared in Example 1 x HER polarization curve of MXene; Figure 7 CeO2-NiCoP / Ti3C2T prepared in Example 1 x Tafel slope obtained by converting the polarization curve of MXene HER catalyst; Figure 8 CeO2-NiCoP / Ti3C2T prepared in Example 1 x Electrochemical impedance spectroscopy of MXene-based HER catalyst; Figure 9 CeO2-NiCoP / Ti3C2T prepared in Example 1 x OER polarization curves of MXene; Figure 10 CeO2-NiCoP / Ti3C2T prepared in Example 1 x Tafel slope obtained by converting the polarization curve of MXene OER catalyst; Figure 11 CeO2-NiCoP / Ti3C2T prepared in Example 1 x Electrochemical impedance spectroscopy of MXene OER catalyst; Figure 12 CeO2-NiCoP / Ti3C2T prepared in Example 1 x MXene's 100 mA / cm -2 HER (a) and OER (b) stability curves under different potentials; Figure 13 NiCoP / Ti3C2T prepared in Comparative Example 1 x SEM images of MXene-1; (a) scale bar is 200 nm, (b) scale bar is 500 nm; Figure 14 NiCoP / Ti3C2T prepared in Comparative Example 1 x HER polarization curve of MXene-1; Figure 15 NiCoP / Ti3C2T prepared in Comparative Example 1 x Tafel slope obtained by converting the polarization curve of MXene-1 HER catalyst; Figure 16 NiCoP / Ti3C2T prepared in Comparative Example 1 x Electrochemical impedance spectroscopy of MXene-1 HER catalyst; Figure 17 NiCoP / Ti3C2T prepared in Comparative Example 1 x OER polarization curve of MXene-1; Figure 18 NiCoP / Ti3C2T prepared in Comparative Example 1 x Tafel slope obtained by converting the polarization curve of MXene-1 OER catalyst; Figure 19NiCoP / Ti3C2T prepared in Comparative Example 1 x Electrochemical impedance spectroscopy of MXene-1 OER catalyst; Figure 20 NiCoP / Ti3C2T prepared in Comparative Example 2 x SEM images of MXene-2; (a) scale bar is 200 nm, (b) scale bar is 500 nm; Figure 21 NiCoP / Ti3C2T prepared in Comparative Example 2 x HER polarization curve of MXene-2; Figure 22 NiCoP / Ti3C2T prepared in Comparative Example 2 x Tafel slope obtained by converting the polarization curve of MXene-2 ​​HER catalyst; Figure 23 NiCoP / Ti3C2T prepared in Comparative Example 2 x Electrochemical impedance spectroscopy of MXene-2 ​​HER catalyst; Figure 24 NiCoP / Ti3C2T prepared in Comparative Example 2 x OER polarization curve of MXene-2; Figure 25 NiCoP / Ti3C2T prepared in Comparative Example 2 x Tafel slope obtained by converting the polarization curve of MXene-2 ​​OER catalyst; Figure 26 NiCoP / Ti3C2T prepared in Comparative Example 2 x Electrochemical impedance spectroscopy of MXene-2 ​​OER catalyst. DETAILED DESCRIPTION

[0016] The present invention will be further described below with reference to the accompanying drawings and specific embodiments.

[0017] In the following examples, unless otherwise stated, all reagents used can be purchased from commercial sources or obtained according to known literature reports. Example 1

[0018] A method for preparing a composite electrocatalytic material of cerium dioxide-doped nickel cobalt phosphide loaded on titanium carbide Mxene comprises the following steps: S1, using hydrochloric acid and lithium fluoride as etchants to etch in a 100 ml polytetrafluoroethylene liner; S1-1. Dissolve 0.077 mol lithium fluoride in 20 mL hydrochloric acid solution (12 mol L -1), magnetically stirred at 30-35 °C for 10-15 min, then 0.0051 mol Ti3AlC2 MAX powder was added, the temperature was raised to 35-40 °C, and stirring was continued at constant temperature for 36-48 h. The entire reaction was carried out in a fume hood; S1-2. Transfer the suspension obtained in step S1-1 to a centrifuge tube and wash several times with deionized water using a centrifuge; initially, centrifuge at 3000 rpm for 5 min, discard the supernatant, and redisperse the precipitate in deionized water by hand-shaking to achieve a certain degree of exfoliation. Increase the speed and time of the washing centrifuge according to actual conditions (within 12000 rpm) until the pH of the supernatant approaches 7, thereby obtaining precipitate I; S2. Dissolve all the precipitate I obtained in step S1 in 20 ml of dimethyl sulfoxide, stir magnetically at room temperature for 18-24 h until the precipitate I is completely dissolved, and wash the dimethyl sulfoxide with deionized water to obtain precipitate II; redisperse precipitate II in deionized water, and ultrasonically peel the multilayer material into a single layer or a few layers of MXene (argon is introduced during this process); to avoid oxidation of MXene during this process, replace ice cubes in time, and keep the ultrasonication process in an ice bath at no more than 20 °C; centrifuge at 8000-10000 r / min, and the dark green upper suspension obtained at this time is the single layer or few layers of Ti3C2T x MXene is collected in a special bottle and placed in the refrigerator for fresh-keeping. A portion is freeze-dried and its concentration is calibrated. S3, the Ti3C2T obtained in step S2 x MXene suspension was diluted to 1 mg mL -1 Then nickel nitrate hexahydrate (1 mmol), cobalt nitrate hexahydrate (2 mmol), cerium nitrate hexahydrate (0.15 mmol), urea (15 mmol) and NH4F (7.5 mmol) were dissolved in 60-70 ml of diluted Ti3C2T x After magnetic stirring for 30-35 min in the MXene suspension, the resulting mixture was transferred to a 100 ml polytetrafluoroethylene-lined autoclave, assembled, and kept at 120 °C for 12 h. The mixture was then washed with deionized water and dried in vacuum at 60 °C. S4: Place the powder obtained in step S3 in a porcelain boat, then place the porcelain boat flat in a tube furnace, introduce Ar, and set the heating rate to 3°C min -1, reduced at 450 °C for 2 h and then cooled to room temperature to obtain a precursor; sodium hypophosphite was used as a P source for phosphating process, sodium hypophosphite was weighed according to the mass ratio of the precursor to sodium hypophosphite of 1:3, the precursor and sodium hypophosphite were placed at both ends of the quartz tube, with sodium hypophosphite at the upstream position, and heated to 350 °C in a tube furnace under Ar atmosphere, and the heating rate was set to 3 °C min -1 , and kept warm for 2 h. When the temperature dropped to room temperature, the target sample was obtained and named CeO2-NiCoP / Ti3C2T x MXene.

[0019] XRD test uses Bruker D8 advance X-ray diffractometer, and adopts grazing incidence method to analyze the phase composition and crystal structure of the material surface. x The lattice structure of MXene composite materials is analyzed. Figure 1 It shows that Ti3C2T x Compared with the XRD of the original material Ti3AlC2, the diffraction peak of MXene corresponding to the (104) crystal plane around 2θ=39° disappears, and the diffraction peak corresponding to the (002) crystal plane around 2θ=9° shifts to a smaller angle. Both indicate that the Al layer in Ti3AlC2 is etched away and the interlayer spacing increases.

[0020] The SEM test was performed using a ZEISS Gemini 300 field emission scanning electron microscope. The powder obtained in this example was dispersed in anhydrous ethanol and evenly dispersed by ultrasound. 5-10 μL of the dispersion was dropped onto a single crystal Si wafer. After drying, it was sprayed with gold and prepared for SEM testing. Figure 2 The results show that, by comparison, CeO2-NiCoP / Ti3C2T x A large number of NiCoP particles were observed on MXene, and they were small in size, too densely distributed, and agglomerated. Ce was not observed because the ratio of the added cerium source was only 5% of the total molar amount of the nickel source and cobalt source. The Ce content was very low, and CeO2 grew on the NiCoP particles or Ti3C2T in the form of doping. x On the surface of MXene. Figure 3 It is shown that the high resolution transmission electron microscopy (HRTEM) images of CeO2-NiCoP / Ti3C2T x Further analysis of the micromorphology of MXene materials proved that the successful formation of the composite interface was beneficial to the bonding between NiCoP and CeO2, as well as between NiCoP, CeO2 and Ti3C2T x Charge transfer between MXenes.

[0021] Verification was performed using HAADF-STEM and elemental mapping distribution. Figure 4 The HAADF-STEM and elemental mapping distributions show more clearly the distribution of C, Ti, P, O, Ce, Co, and Ni, among which Ni and Co coordinate with each other to form NiCoP, which is evenly distributed in the Ti3C2T x On the surface of MXene, Ce and O coordinate to form CeO2, but the content is relatively low, only 2.47 wt%. CeO2 grows on NiCoP in the form of doping, and there may also be some CeO2 growing on Ti3C2T x On MXene. Figure 5 The Ce signal peak is seen in the EDS image, which further verifies that CeO2 is successfully prepared. The above is enough to prove that CeO2-NiCoP particles are successfully prepared and attached to Ti3C2T x On MXene sheets.

[0022] CeO2-NiCoP / Ti3C2T was tested by three-electrode system. x MXene was measured. The specific steps are as follows: the CeO2-NiCoP / Ti3C2T prepared in this example x MXene was clamped on a platinum electrode clamp as the working electrode, Ag / AgCl was used as the reference electrode, and a carbon rod was used as the counter electrode to conduct the HER polarization curve test in 1 mol KOH solution. -1 At the same scan rate, linear sweep voltammetry (LSV) was used to measure the polarization curves multiple times until the obtained data curves were close to overlap. The initial and final potential ranges of the HER test were -1V~-2V. The frequency range of the start and end of the electrochemical impedance spectroscopy (EIS) was 10 5 Hz-10 -2 Hz, CeO2-NiCoP / Ti3C2T x The CV curves of the MXene catalyst were tested in the voltage range of 0.505~0.605 V vs. RHE and 0.556~0.656 V vs. RHE, with a scan rate range of 50~100 mV s -1 .like Figure 6 It shows that for HER performance test, CeO2-NiCoP / Ti3C2T x The overpotential corresponding to MXene is small, only 147 mV; Figure 7 It shows that the Tafel slope is 134 mV dec -1 ;like Figure 8 It shows that CeO2-NiCoP / Ti3C2T x MXene has a small semicircular diameter, which indicates that its charge transfer resistance is small and the charge transfer rate is fast; Figure 9 It shows that for OER performance test, CeO2-NiCoP / Ti3C2T x The overpotential corresponding to MXene is small, only 287 mV; Figure 10 This shows that the Tafel slope is 64 mV dec. -1 , indicating good reaction kinetics and high catalytic activity of the material. This material has low charge transfer resistance, such as Figure 11 It shows that the corresponding arc radius is very small, indicating that the faster the charge transfer speed is, the faster the corresponding reaction kinetics is. Figure 12 It shows that CeO2-NiCoP / Ti3C2T x The stability test of MXene for HER in alkaline medium showed excellent hydrogen evolution activity, which can reach 10 mA cm -2 The electrode activity was maintained at 84.6% when the reaction was continued for 25 h near the current density. The oxygen evolution activity was also excellent. After a 25-h It OER durability test, the current density was maintained at 10 mA cm -2 There is almost no loss near the catalyst, and the electrode activity can still be maintained at 93.6%, indicating that the catalyst has excellent stability in HER and OER under alkaline conditions.

[0023] Comparative Example 1 A NiCoP / Ti3C2T x The preparation method of MXene-1 composite material comprises the following steps: S1, keep consistent with Example 1; S2, keep consistent with Example 1; S3, the Ti3C2T obtained in step S2 x MXene suspension was diluted to 1 mg mL -1 Then nickel nitrate hexahydrate (2 mmol), cobalt nitrate hexahydrate (1 mmol), urea (15 mmol) and NH4F (7.5 mmol) were dissolved in 60-70 ml of diluted Ti3C2T x After magnetic stirring for 30-35 min in the MXene suspension, the resulting mixture was transferred to a 100 ml polytetrafluoroethylene-lined autoclave, assembled, and kept at 120 °C for 12 h. The mixture was then washed with deionized water and dried in vacuum at 60 °C. S4. Keep the same as in Example 1 to obtain the target sample, named NiCoP / Ti3C2T x MXene-1.

[0024] The SEM test was performed using a ZEISS Gemini 300 field emission scanning electron microscope. The powder obtained in this comparative example was dispersed in anhydrous ethanol, and the powder was evenly dispersed by ultrasound. 5-10 μL of the dispersion was dropped onto a single crystal Si wafer, and after drying, it was sprayed with gold and prepared for SEM testing. Figure 13 The SEM results show that a large number of NiCoP particles were generated, and the size was extremely small, the distribution was too dense, and agglomeration occurred. By comparison, it was found that the particles were slightly smaller than those in Example 1, which was because no Ce source was added.

[0025] The NiCoP / Ti3C2T x MXene-1 was measured. The specific steps are as follows: NiCoP / Ti3C2T x MXene-1 was clamped on a platinum electrode clamp as the working electrode, Ag / AgCl was used as the reference electrode, and a carbon rod was used as the counter electrode to conduct the HER polarization curve test in 1 mol KOH solution. -1 At the same scan rate, linear sweep voltammetry (LSV) was used to measure the polarization curves multiple times until the obtained data curves were close to overlap. The initial and final potential ranges of the HER test were -1V~-2V. The frequency range of the start and end of the electrochemical impedance spectroscopy (EIS) was 10 5 Hz-10 -2 Hz, NiCoP / Ti3C2T x The CV curves of the MXene-1 catalyst were tested in the voltage range of 0.505~0.606 V vs. RHE, with a scan rate range of 50~100 mV s -1 .like Figure 14 It shows that for HER performance test, NiCoP / Ti3C2T x The overpotential corresponding to MXene-1 is small, only 202 mV, such as Figure 15 It shows that the Tafel slope is 164 mV dec -1 ;like Figure 16 It shows that NiCoP / Ti3C2T x MXene-1 has a smaller semicircular diameter, indicating that its charge transfer resistance is small and the charge transfer rate is fast, but its performance is worse than that of Example 1. Figure 17 It shows that for OER performance test, NiCoP / Ti3C2T x The overpotential corresponding to MXene-1 is small, 358 mV; Figure 18 It shows that the Tafel slope is 146 mV dec -1 , indicating good reaction kinetics, high catalytic activity of the material, and low charge transfer resistance. Figure 19 It shows that NiCoP / Ti3C2T x MXene-1 has a smaller arc radius, but a slightly larger radius than Example 1. Its charge transfer speed is faster, and the corresponding reaction kinetics is also faster. x The performance of MXene-1 shows a downward trend, indicating that the x On the MXene matrix material, the rare earth oxide CeO2 can give full play to its advantages such as good stability, good hydrophilicity, strong oxygen storage capacity, reversible exchange of surface oxygen ions and good electronic / ionic conductivity. It can be used as a promoter to adjust the electrocatalytic performance of various transition metals and optimize the catalytic activity of phosphides (NiCoP). Compared with Example 1, this comparative example lacks a Ce source, so there is a trend of performance decline.

[0026] Comparative Example 2 A NiCoP / Ti3C2T x The preparation method of MXene-2 ​​composite material comprises the following steps: S1, keep consistent with Example 1; S2, keep consistent with Example 1; S3, the Ti3C2T obtained in step S2 x MXene suspension was diluted to 1 mg mL -1 Then nickel nitrate hexahydrate (1 mmol), cobalt nitrate hexahydrate (2 mmol), urea (15 mmol) and NH4F (7.5 mmol) were dissolved in 60-70 ml of diluted Ti3C2T x After magnetic stirring for 30-35 min, the resulting mixture was transferred to a 100 ml polytetrafluoroethylene-lined autoclave, assembled, and kept at 120 °C for 12 h. The mixture was then washed with deionized water and dried in vacuum at 60 °C. S4. Keep the same as in Example 1 to obtain the target sample, named NiCoP / Ti3C2T x MXene-2.

[0027] The SEM test was performed using a ZEISS Gemini 300 field emission scanning electron microscope. The powder obtained in this comparative example was dispersed in anhydrous ethanol, and the powder was evenly dispersed by ultrasound. 5-10 μL of the dispersion was dropped onto a single crystal Si wafer, and after drying, it was sprayed with gold and prepared for SEM testing. Figure 20The SEM results show that a large number of NiCoP particles are generated, and the size is extremely small and the distribution is too dense. The NiCoP particle size is relatively increased. Although the particles are still agglomerated, the particle distribution is not as tight as that of Comparative Example 1, which is almost the same as that of Example 1. This may be because the proportion of cerium source added in Example 1 is only 5% of the total molar amount of nickel source and cobalt source, and the Ce content is very low. CeO2 grows on NiCoP particles or Ti3C2T in the form of doping. x on the surface of MXene.

[0028] The NiCoP / Ti3C2T x MXene-2 ​​was measured. The specific steps are as follows: NiCoP / Ti3C2T x MXene-2 ​​was clamped on a platinum electrode clamp as the working electrode, Ag / AgCl was used as the reference electrode, and a carbon rod was used as the counter electrode to conduct the HER polarization curve test in 1 mol KOH solution. -1 At the same scan rate, linear sweep voltammetry (LSV) was used to measure the polarization curves multiple times until the obtained data curves were close to overlap. The initial and final potential ranges of the HER test were -1V~-2V. The frequency range of the start and end of the electrochemical impedance spectroscopy (EIS) was 10 5 Hz-10 -2 Hz, NiCoP / Ti3C2T x The CV curves of the MXene-2 ​​catalyst were tested in the voltage range of 0.505~0.606 V vs. RHE, with a scan rate range of 50~100 mV s -1 .like Figure 21 It shows that for HER performance test, NiCoP / Ti3C2T x The overpotential corresponding to MXene-2 ​​is small, only 167 mV, such as Figure 22 It shows that the Tafel slope is 147 mV dec. -1 ;like Figure 23 It shows that NiCoP / Ti3C2T x MXene-2 ​​has a smaller semicircle diameter, indicating that its charge transfer resistance is small and the charge transfer rate is fast. Compared with Comparative Example 1, the semicircle diameter is smaller, but the performance is worse than that of Example 1. Figure 24 It shows that for OER performance test, NiCoP / Ti3C2T x The overpotential corresponding to MXene-2 ​​is small, 331 mV; Figure 25 It shows that the Tafel slope is 81 mV dec -1 , indicating good reaction kinetics, high catalytic activity of the material, and low charge transfer resistance. Figure 26 It shows that NiCoP / Ti3C2T x The arc radius of MXene-2 ​​is smaller, indicating that its charge transfer rate is faster and the corresponding reaction kinetics is faster. The arc radius is slightly smaller than that of Comparative Example 1, but compared with Example 1, NiCoP / Ti3C2T x The performance of MXene-2 ​​shows a downward trend, indicating that the x On a MXene matrix, the rare earth oxide CeO2 leverages its inherent advantages, including excellent stability, hydrophilicity, strong oxygen storage capacity, reversible surface oxygen ion exchange, and excellent electronic and ionic conductivity. It can be used as a promoter to modulate the electrocatalytic performance of various transition metals and optimize the catalytic activity of NiCoP. This comparative example, compared to Example 1, lacks a Ce source, resulting in a decline in performance. It is believed that CeO2 doping facilitates charge transfer and reduces the overpotential required for the hydrogen and oxygen evolution reactions.

Claims

1. A method for preparing a composite electrocatalytic material of cerium dioxide doped nickel cobalt phosphide loaded on titanium carbide Mxene, characterized in that: The following steps are involved: S1, using hydrochloric acid and lithium fluoride as etchants to etch in a polytetrafluoroethylene liner; S1-1. Dissolve lithium fluoride in an appropriate amount of hydrochloric acid solution and stir at 30-35°C for 10-15 minutes. Then add Ti3AlC2MAX powder, raise the temperature to 35-40°C, and stir continuously at constant temperature for 36-48 hours to obtain a suspension. The entire reaction is carried out in a fume hood. S1-2, transferring the suspension obtained in step S1-1 to a centrifuge tube, and washing the suspension several times with deionized water through a centrifuge until the pH of the supernatant is 6.8-7, thereby obtaining precipitate I; S2. The precipitate I obtained in step S1 was dissolved in dimethyl sulfoxide, stirred at room temperature, and then the dimethyl sulfoxide was washed with deionized water to obtain precipitate II. The precipitate II was redispersed in deionized water and sonicated in the presence of argon to peel the multilayer material into a single layer or a few layers of MXene. The dark green upper suspension obtained by centrifugation was the single layer or few layers of Ti3C2T x MXene; S3, the Ti3C2T obtained in step S2 x The MXene suspension was diluted, and then nickel nitrate hexahydrate, cobalt nitrate hexahydrate, cerium nitrate hexahydrate, urea and NH4F were dissolved in an appropriate amount of diluted Ti3C2T x After magnetic stirring, the resulting mixture was transferred to an autoclave and kept at 110-130 °C for 10-14 h. It was then washed with deionized water and dried under vacuum. S4. The powder obtained in step S3 is placed in a tube furnace, Ar is introduced, and the mixture is reduced at 400-500°C for 1-3 hours, and then cooled to room temperature to obtain a precursor; a phosphating process is performed using sodium hypophosphite as a P source, and the precursor and sodium hypophosphite are placed at both ends of a quartz tube, with the sodium hypophosphite at the upstream position. The mixture is heated to 300-400°C in a tube furnace under Ar atmosphere, kept warm for 1-2 hours, and cooled to room temperature to obtain the target sample, which is named CeO2-NiCoP / Ti3C2T x MXene.

2. The method for preparing a cerium dioxide-doped nickel cobalt phosphide loaded on titanium carbide Mxene composite electrocatalytic material according to claim 1, characterized in that: In step S4, the mass ratio between the precursor and sodium hypophosphite is 1:3; the heating rate in the tube furnace is set to 3°C min -1 .

3. The method for preparing a cerium dioxide-doped nickel cobalt phosphide loaded on titanium carbide Mxene composite electrocatalytic material according to claim 1 or 2, characterized in that: In step S4, the precursor is obtained by reducing the mixture at 450°C for 2 h and then cooling the mixture to room temperature.

4. The method for preparing a cerium dioxide-doped nickel cobalt phosphide loaded on titanium carbide Mxene composite electrocatalytic material according to claim 1 or 2, characterized in that: In step S4, the quartz tube is heated to 350° C. in a tube furnace under an Ar atmosphere and kept at this temperature for 2 h.

5. The method for preparing a cerium dioxide-doped nickel cobalt phosphide loaded on titanium carbide Mxene composite electrocatalytic material according to claim 1 or 2, characterized in that: In step S3, the concentrations of nickel nitrate hexahydrate, cobalt nitrate hexahydrate, cerium nitrate hexahydrate, urea, and NH4F in the mixed solution are 0.014-0.017 mol / L, 0.028-0.034 mol / L, 0.002-0.0025 mol / L, 0.21-0.25 mol / L, and 0.1-0.125 mol / L, respectively; the mixture is kept at 120°C for 12 hours, stirred for 30-35 minutes, and dried in vacuo at 60°C.

6. The method for preparing a cerium dioxide-doped nickel cobalt phosphide loaded on titanium carbide Mxene composite electrocatalytic material according to claim 1 or 2, characterized in that: In step S2, the ultrasonication is performed in an ice bath throughout the entire process, with the ultrasonication temperature below 20° C.; and the centrifugal speed is 8000-10000 r / min.

7. The method for preparing a cerium dioxide-doped nickel cobalt phosphide-loaded titanium carbide Mxene composite electrocatalytic material according to claim 1 or 2, characterized in that: In step S1-1, the molar ratio of Ti3AlC2 MAX powder to lithium fluoride and hydrochloric acid is 1:15:

47.

8. The method for preparing a cerium dioxide-doped nickel cobalt phosphide-loaded titanium carbide Mxene composite electrocatalytic material according to claim 1 or 2, characterized in that: In step S1-2, the centrifugal speed is 3000-12000 r / min, and the centrifugal time is 5-20 min.

9. A composite electrocatalytic material comprising cerium dioxide-doped nickel cobalt phosphide loaded on titanium carbide (MXene) prepared by the method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Preparation method of MXene / NiCoP / NF composite material

    CN113096972A

  • Iron-doped nickel cobalt phosphide and molybdenum trioxide compounded electrolyzed water bifunctional catalyst and preparation method thereof

    CN115928102A

  • CoFeP / MXene oxygen evolution electro-catalysis composite material as well as preparation method and application thereof

    CN116876007A

  • Bifunctional electrolyzed water catalyst as well as preparation method and application thereof

    CN116905039A

  • MXene-based difunctional electro-catalytic material as well as preparation and application thereof

    CN118727041A

Cited By

  • Phosphorus-doped iridium tantalum cerium bifunctional electrode and preparation method and application thereof

    CN122214945A